Implementasi Matriks Augmented dan Metode Eliminasi Gauss-Jordan untuk Menyelesaikan Masalah GPS (Studi Kasus: Menentukan Posisi Pejalan Kaki yang Tersesat) - Mufid, Nadiya Azhar (Jurnal Pendidikan Matematika, 2023)
The Global Positioning System (GPS) is a satellite-based navigation system that enables users to determine their position and time anywhere near the Earth's surface. GPS calculates distance by knowing how long it takes for a radio signal to move from one point to another. Linear algebra, especially augmented matrices and the Gauss-Jordan elimination method, can be applied to solve GPS problems in the case study of a pedestrian lost in the desert. The position of a lost pedestrian in a desert will be determined based on satellite position and time data. The calculation results indicate that the position of the lost pedestrian is in the Bilma desert area, Agadez district, Niger, with coordinates at a longitude of 11.41199 and a latitude of 18.549.